Periodate activation with manganese oxides for sulfanilamide degradation. (1st February 2020) - Du, Jiangkun; Xiao, Guangfeng; Xi, Yanxing; Zhu, Xiaowei; Su, Fan; Kim, Sang Hoon
Abstract: This study presents a novel periodate oxidation system mediated by manganese oxides for the rapid removal of aqueous contaminants. The catalytic activation of periodate on manganese oxides was demonstrated as an efficient advanced oxidation system for degradation of sulfanilamide. The reactivity of manganese oxides with different Mn valence followed the order of MnO2 >Mn3 O4 >Mn2 O3, all of which showed extraordinary reusability during repeated activation of periodate. Sulfanilamide was rapidly degraded along with stoichiometric transformation of IO4 − to IO3 −, and both processes exhibited good linear correlations with the dosage of manganese oxides. While the degradation of sulfanilamide in the MnO2 /IO4 − system was accelerated at lower solution pH, it was only slightly affected by ionic strength, water anions and humic acid. In contrast to the homogeneous system of Mn 2+ /IO4 −, sulfanilamide degradation was not influenced in oxic and anoxic environment. It was evidenced by quenching studies and EPR tests that both singlet oxygen ( 1 O2 ) and iodate radicals (IO3 ) were generated when the metastable Mn(IV)-O-IO3 interacted with sulfanilamide. The XPS spectra of Mn 2p and O 1s before and after reactions indicated that the catalytic activation of periodate on MnO2 was not in company with the redox cycling of Mn(IV) species. Graphical abstract: Image 1 Highlights: MnO2 -activated periodate was a highly efficient and reusable heterogeneous process for sulfanilamide degradation. The evolution of 1 O2 and surface bound IO3 were unveiled to be oxidizing species. IO4 − stoichiometrically converted to IO3 − with good mass balance.